A study on the assessment of the resilience of agricultural system under flood disaster. Issue 1 (June 2020) - Song, Liangliang; Li, Ying; Long, Rui; Tong, Linchen; Zhang, Jinghe; Zhu, Xinuo
Abstract: In order to further understand the flood control and disaster resistance ability of agricultural system, the concept of resilience of agricultural system under flood and waterlogging disaster is given. From four aspects of technology, economy, environment and society, the most representative eight evaluation indexes are selected to build the resilience model of agricultural system under flood disaster, determine the grade standard of each index, introduce TOPSIS method and adopt "two-level empowerment" to quantify the resilience of agricultural system under flood disaster. Taking 13 cities in Jiangsu Province as an example, this paper uses the TOPSIS based assessment model to assess the resilience of agricultural system under flood and waterlogging disasters, and the assessment results are consistent with the actual situation.